Pencegahan Stunting Melalui Peningkatan Pengetahuan Calon Pengantin tentang Prediksi Tinggi, Berat badan Balita Serta Berat Badan Ibu Hamil di Desa Notorejo Kecamatan Gondang Kabupaten Tulungagung - Djunawan, Achmad; Mujiburrahman, M. Alexander; Rizki, M. Risya; Puriyanti, Puriyanti (Jurnal Abdimas Jatibara, 2025)
Stunting is a chronic nutritional problem in toddlers indicated by low weight and height of toddlers. Stunting is a chronic nutritional problem in toddlers indicated by low weight and height of toddlers. Therefore, efforts are needed to prevent stunting with the active involvement of all components of society. This study aims to improve the understanding of prospective brides and grooms regarding the prediction of toddler weight and height and the weight of pregnant women with a counseling method through material presentation. The results of this counseling are that the knowledge of prospective brides increased by 4.3 points. So that with the counseling, it can increase the knowledge of prospective brides about the prediction and prevention of stunting.